Decentralization of schools in South Africa: a study of two SGBs - Melaphi, Nompumelelo (My University, 2016)
The aim of this research was to analyze the restructuring of the post-apartheid South African education system through the decentralization introduced in the South African Schools Act of 1996 (SASA). SASA was intended to construct a new education landscape for school governance involving School Governing Bodies (SGBs) and founded on participation and partnership between state, parents, learner, school staff and community. SASA ostensibly bestowed powers upon the SGBs, however this research explores whether the schools used in the study were really empowered by SASA. Two schools were investigated, one in an affluent area and the other in an underprivileged area. The investigation was in context of the impact of decentralisation of service delivery in developing countries, the adoption of SASA and reforms in the education system from apartheid to date. A qualitative methodology was used and analysis of fourteen semi-structured interviews produced four findings. First, the study corroborated others which suggest that neoliberalism is imbedded in South African public schools and that parents have to pay for quality education. Second, the SGB from the Privileged School executed their projects and tasks well as compared to the Underprivileged School, since its SGB involved parents that were professionals, with financial backing and the know how to fund raise so that the school was able to provide resources for the learners. Third, the minimal use of SASA powers was not the sole reason for inequality in educational provision, the study also looked into the apartheid historical past which also contributed to inequality Finally the post-apartheid (Bantu) education system was a contributing factor to the Underprivileged School SGB’s incapability to utilise all its powers in that ‘Bantu education’ had failed to equip parents from underprivileged backgrounds with the knowledge to exercise all the powers granted to them by SASA, in particular, most parent/s from the underprivileged school had not been equipped with professional degrees or acquired significant skills to confidently partake in the SGB. The study concludes that SASA seems to have not fully taken cognisance of the realities of SGBs in the Underprivileged School since it seems likely, based on my single case study, that their members would not be able to fully implement all the powers given to them by SASA, indicating the need for state intervention.
A research report submitted in partial fulfilment of the requirements for the Master’s Degree in Development Theory and Policy University of the Witwatersrand 31 March 2015
Keywords: School management and organization--South Africa; Schools--Decentralization--South Africa; Education and state--South Africa